Foreign body embedded in the esophageal wall as a cause of dysphagia and regurgitation in a 16-month-old child: a case report and mini review - Czerwiec, Bartłomiej; Skowrońska-Borsuk, Julia; Janiga, Tomasz; Dembiński, Łukasz; Banasiuk, Marcin (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Esophageal foreign bodies are a common clinical finding; however, transmural embedding of a foreign object into the esophageal wall is rare. In pediatric patients, the diagnosis may be particularly challenging due to non-specific and diverse symptomatology. Clinical manifestations of an esophageal foreign body may include regurgitation, odynophagia, or vomiting during food intake. This article described the case of a patient suspected of having a foreign body embedded in the esophageal wall, who primarily presented with symptoms of regurgitation during eating. We aimed to emphasize the importance of proper diagnosis and diagnostic procedures as well as increasing awareness of this condition. Additionally, the article included a brief literature review of pediatric cases with varied clinical presentations despite similar diagnosis.